Priority based Proactive Buffer Management for Aggregated Streaming in Heterogeneous Wireless Networks - Duraimurugan, S; Jesu Jayarin, P (International Journal of Engineering and Technology, 2018)
Now a days, most of the data is transmitted between two devices using Wireless network. Although this has made it easier to transmit data, it also has its disadvantages. One of its disadvantage being the irregular data transfer due to the presence of congestion in the intermediate nodes. This paper proposes an idea to overcome the said disadvantage by developing a priority based proactive buffer management for the wireless network through the use of buffer which will be maintained at the source. The buffer is used to regulate the transmission rate of the data packets in accordance with the congestion level which is present in the transmission path. For faster transmission, the data packets having high priority are transmitted while the data packets having lower priority are dropped thereby reducing the quantity of data packets being transmitted, hence overcoming the problem of congestion.Â